Determination of spinal tracer dispersion after intrathecal injection in a deformable CNS model - Ayansiji, Ayankola O.; Gehrke, Daniel S.; Baralle, Bastien; Nozain, Ariel; Singh, Meenesh R.; Linninger, Andreas A. (Frontiers in Physiology, 2023)
Background Traditionally, there is a widely held belief that drug dispersion after intrathecal (IT) delivery is confined locally near the injection site. We posit that high volume infusions can overcome this perceived limitation of IT administration. Methods To test our hypothesis, subject-specific deformable phantom models of the human central nervous system were manufactured so that tracer infusion could be realistically replicated in vitro over the entire physiological range of pulsating cerebrospinal fluid (CSF) amplitudes and frequencies. Distribution of IT injected tracers was studied systematically with high-speed optical methods to determine its dependence on injection parameters (infusion volume, flow rate, catheter configurations) and natural CSF oscillations in a deformable model of the central nervous system (CNS). Results Optical imaging analysis of high-volume infusion experiments showed that tracers spread quickly throughout the spinal subarachnoid space (SAS), reaching the cervical region in less than ten minutes. The experimentally observed biodispersion is much slower than suggested by the Taylor-Aris-Dispersion (TAD) theory. Our experiments indicate that micro-mixing patterns induced by oscillatory CSF flow around microanatomical features such as nerve roots significantly accelerate solute transport. Strong micro mixing effects due to anatomical features in the spinal subarachnoid space were found to be active in intrathecal drug administration but were not considered in prior dispersion theories. Their omission explains why prior models developed in the engineering community are poor predictors for IT delivery. Conclusion Our experiments support the feasibility of targeting large sections of the neuroaxis or brain utilizing high-volume IT injection protocols. The experimental tracer dispersion profiles acquired with an anatomically accurate, deformable, and closed in vitro human CNS analog informed a new predictive model of tracer dispersion as a function of physiological CSF pulsations and adjustable infusion parameters. The ability to predict spatiotemporal dispersion patterns is an essential prerequisite for exploring new indications of IT drug delivery that targets specific regions in the central nervous system (CNS) or the brain.